2015
DOI: 10.1016/j.molmet.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic disruption of uncoupling protein 1 in mice renders brown adipose tissue a significant source of FGF21 secretion

Abstract: ObjectiveCirculating fibroblast growth factor 21 (FGF21) is an important auto- and endocrine player with beneficial metabolic effects on obesity and diabetes. In humans, thermogenic brown adipose tissue (BAT) was recently suggested as a source of FGF21 secretion during cold exposure. Here, we aim to clarify the role of UCP1 and ambient temperature in the regulation of FGF21 in mice.MethodsWildtype (WT) and UCP1-knockout (UCP1 KO) mice, the latter being devoid of BAT-derived non-shivering thermogenesis, were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
78
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 30 publications
19
78
1
Order By: Relevance
“…After adiponectin treatment, decreased BAT activity, metabolic abnormalities, acyclicity, and abnormal hormonal levels were surprisingly normalized up to normal levels in the PCOS rat. Based on recent publications, BAT also secretes a considerable number of adipokines, such as adiponectin, FGF21, NGF, NRG4, VEGF, and BMPs (16,35). We have observed that there was no significant difference of FGF21 or NGF levels between groups (Table S6).…”
Section: Discussionmentioning
confidence: 71%
“…After adiponectin treatment, decreased BAT activity, metabolic abnormalities, acyclicity, and abnormal hormonal levels were surprisingly normalized up to normal levels in the PCOS rat. Based on recent publications, BAT also secretes a considerable number of adipokines, such as adiponectin, FGF21, NGF, NRG4, VEGF, and BMPs (16,35). We have observed that there was no significant difference of FGF21 or NGF levels between groups (Table S6).…”
Section: Discussionmentioning
confidence: 71%
“…Despite these discrepancies, these results indicate that FGF21 may promote energy expenditure through mechanisms other than the induction of UCP1-mediated uncoupling respiration in brown or beige/brite adipocytes. In fact, UCP1-null mice show a dramatic increase in FGF21 levels and FGF21 expression in BAT and WAT (Keipert et al, 2015;Samms et al, 2015), suggestive of homeostatic compensatory mechanisms for promotion of energy expenditure when the UCP1-mediated mechanisms are blunted.…”
Section: Fgf21: Activator Of Brown Adipose Tissue and "Browning"mentioning
confidence: 99%
“…However, when UCP1 is absent in UCP1-null mice, FGF21 decrease appetite and food intake resulting in weight loss as well [61,116]. Interestingly, UCP1-null mice showed impressive increment in FGF21 levels with very high expression in BAT and WAT [61,117]. Therefore, FGF21 is an important compensatory mechanism when UCP1 mechanism is diminished, and anti-obesity effect do not necessarily involve the generation of brown adipocytes in WAT and UCP1 activity in mice [116].…”
Section: "Browning" Of Watmentioning
confidence: 99%